2008
DOI: 10.1007/s11606-008-0584-2
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Health Care Disparities Curriculum for Incoming Medical Students

Abstract: PURPOSE: 1) To pilot a health disparities curriculum for incoming first year medical students and evaluate changes in knowledge. 2) To help students become aware of personal biases regarding racial and ethnic minorities. 3) To inspire students to commit to serving indigent populations.METHODS: First year students participated in a 5-day elective course held before orientation week. The course used the curricular goals that had been developed by the Society of General Internal Medicine Health Disparities Task F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
81
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 12 publications
0
81
1
Order By: Relevance
“…The tour’s strategy of exposing students to local communities affected by health disparities, a teaching methodology supported in the literature [26,27], also benefited students’ sense of preparation for future clinical work in community settings. Responding to expert suggestion that medical students develop the skills and intuition necessary to elicit information about patients’ social and cultural contexts, the fact that this community tour was located in neighborhoods in which many of the academic health center’s patients live provided some students with preparation and greater insight into how to care for patients they would soon be encountering during clinical rotations.…”
Section: Discussionmentioning
confidence: 99%
“…The tour’s strategy of exposing students to local communities affected by health disparities, a teaching methodology supported in the literature [26,27], also benefited students’ sense of preparation for future clinical work in community settings. Responding to expert suggestion that medical students develop the skills and intuition necessary to elicit information about patients’ social and cultural contexts, the fact that this community tour was located in neighborhoods in which many of the academic health center’s patients live provided some students with preparation and greater insight into how to care for patients they would soon be encountering during clinical rotations.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16][17][31][32][33][35][36][37] Our findings suggest that trainees' engagement with structural forces and their downstream effects deepens when they share concepts and vocabulary for recognizing and describing such phenomena. Structural competency appears to be a promising foundation for developing this shared understanding.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] The influence of such inequities on health has long been noted by clinicians and public health practitioners, but such content has been incorporated unevenly into medical education and clinical training. [7][8][9][10][11][12][13][14][15][16] Proposed by clinicians and scholars in the medical social sciences, a Bstructural competency^framework calls for a Bshift in medical education…toward attention to forces that influence health outcomes at levels above individual interactions.^1 7(p. 126-27) BStructures^or Bsocial structures^in this sense indicate the policies, economic systems, and other institutions (policing and judicial systems, schools, etc.) that have produced and maintain social inequities and health disparities, often along the lines of social categories such as race, class, gender, and sexuality.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously described the course in detail. 18 In brief, the course follows the curricular aims of the Society of General Internal Medicine Disparities Task Force. The course includes didactic lectures, small group discussions and site visits to local emergency rooms, hospitals, community clinics and community health organizations.…”
Section: Course Descriptionmentioning
confidence: 99%
“…We previously reported that it has been the highest rated course in the medical school, and that it improved students' knowledge and attitudes regarding health disparities. 18 This follow-up study aims to determine if (1) knowledge of the existence of the course influenced minority college students' decision to matriculate to the University of Chicago Pritzker School of Medicine and (2) the course was associated with an increasing percentage of under-represented minority students in the matriculating classes of 2007 and 2008.…”
mentioning
confidence: 99%